Effects of a home-based aromatherapy programme for the management of behavioural and psychological symptoms of dementia among older persons with dementia: A randomised controlled trial with process evaluation - Becky Siu Yin Li; Ankie Tan Cheung; Ka Ming Chow; Carmen Wing Han Chan (Integrative Medicine Research)
Background: Behavioural and psychological symptoms of dementia (BPSD) significantly affect older persons with dementia (OPWDs) and their family caregivers. Inhalation aromatherapy is a safe and effective non-pharmacological approach for BPSD management, but it has not been tested in home-based setting for the Chinese population. This study examined the effects of home-based family caregiver-delivered aromatherapy programme on OPWDs and family caregiver. Methods: Eighty OPWD-family caregiver dyads were randomised (1:1) to either aromatherapy programme or wait-list control. The programme involved 1-hour training for caregivers, and 3-week caregiver-delivered aromatherapy intervention for OPWDs, using inhalation of lavender essential oil twice a day. A comprehensive process evaluation was conducted to evaluate programme implementation and participants’ perceptions. The primary outcome was the severity of BPSD in OPWDs, with secondary outcomes being OPWDs’ quality of life (QoL) and caregivers’ distress and care burden. Results: The OPWDs in the intervention group exhibited significantly decreased severity of disinhibition and irritability/lability (two of the BPSD) and improvements in the health and well-being and social relationships domains of QoL. Caregivers also exhibited decreased distress and care burden, but the differences were not statistically significant. The process evaluation revealed that most participants accepted aromatherapy well, and most caregivers were willing to continue aromatherapy after the study. Conclusion: This study demonstrated that aromatherapy is feasible and effective for managing BPSD in a home-based setting, providing a valuable reference for future research and nursing practice in home-based dementia care. Trial registration: This study was registered at ClinicalTrials.gov (NCT05032664) and Chinese Clinical Trial Registry (ChiCTR2100050869).